Relationship Between Nitrogenous Wastes, Organic Matter, Bacteri-al Abundance, and Protozoan Abundance in Whiteleg Shrimp Inten-sive Farming Ponds - Diah Ayu Satyari Utami; Anik Kusmiatun; Ilham; Desy Febrianti; I Nyoman Sudiarsa; Mohsan Abrori; Andina Chairun Nisa; Annisa Khairani Aras; Diklawati Jatayu; Yasinta Ega Kaborang; I Gusti Ayu Budiadnyani; I Made Aditya Nugraha; Budi Rianto Wahidi; Wahyu (Journal of Aquaculture and Fish Health, 2026)
Whiteleg shrimp (Litopenaeus vannamei) dominates global aquaculture production due to its adaptability to intensive systems. However, intensive systems often experience excess accumulation of nitrogenous waste and total organic matter (TOM), which can destabilize microbial communities and affect water quality. While protozoa are known as bioindicators, few studies have explored how their functional composition interacts with nitrogen cycling and production performance in shrimp ponds. This study investigated the relationships between nitrogenous compounds, TOM, bacterial and protozoan abundance in two intensive shrimp ponds (HP: high protozoan abundance and LP: low protozoan abundance). Water quality parameters, including Total Ammonia Nitrogen (TAN), nitrite, nitrate, TOM, and phosphate, were monitored weekly alongside microbial assessments of total bacterial count (TBC), total Vibrio count (TVC), and protozoa abundance. Protozoa were identified microscopically, while shrimp performance was measured by growth, feed conversion ratio (FCR), survival, and productivity. TOM emerged as the primary ecological driver, significantly correlating with Vibrio abundance (r = 0.585, p < 0.05). Although the high-protozoa pond featured greater bacterial biomass and more bacterivorous taxa (e.g., Ciliata, Vorticella), it had lower shrimp productivity. Conversely, the low-protozoa pond dominated by detritivores (Euplotes, Strombidionopsis) achieved superior growth, FCR, and final biomass, despite higher TOM and nitrite levels. These findings suggest that protozoan functional composition, rather than total abundance, critically influences nutrient cycling, microbial stability, and production outcomes. Managing TOM and fostering beneficial microbial loops are essential strategies for sustainable shrimp farming.